Regional Learning Networks in Medium-Tech Technologies and European Integration - Riccardo Cappellin; Luigi Orsenigo (European Regional Science Association (ERSA), 2006)
The paper aims at investigating the transfer of tacit knowledge both at the regional and at the interregional level and it focuses on the factors and forms of the processes of interactive learning between small and medium size in medium technology sectors. The analysis proceeds from the contributions of four strands of literature, focusing on economics of agglomeration, cognitive economics, industrial strategic alliances and governance in a knowledge economy. While industrial economics interprets technology spill-over at the local level as an automatic and chaotic process allowed by geographical proximity of the firms, regional economics identifies different specific types of flows and networks, which link together in an organized way the various firms and other private and public actors within a given regional innovation system. Cognitive economics may bring a significant contribution, as it considers the relevance for economics of human cognitive aspects and it discovers the key role in the creation of new ideas of selected factors, such as the stimulus by changes in the external environment, the process of "neurognosis" or negative reaction aiming to the protection of the internal integrity, the search process constrained by cognitive proximity, the success in pattern making and the achievement of consistency and compatability, the process of "exaptation" or reconversion leading to path-dependency, the creation of new connections and routines and institutions, which allows to save the limited cognitive capacity of individuals and organizations. This theoretical framework in the analysis of the processes of knowledge creation may be schematically represented through the model of "Territorial Knowledge Management", which aims at promoting the interactive learning processes within the regional innovation systems and focuses on a selected list of knowledge levers, such as: market orientation, accessibility, receptiveness, common identity, creativity and governance. On the base of these theoretical concepts and tools, the paper analyses various case studies of firms embedded in different industrial clusters in Europe, focusing on the forms of the process of interactive learning and innovation between the various regional actors. Finally, the paper attempts to derive from that analysis useful indications for the possible extension of knowledge and innovation networks at the interregional and international level and for decreasing the regional divide in a modern knowledge economy. The research has been undertaken within the framework of the project: "IKINET – International Knowledge and Innovation Network" (EU FP6, N° CIT2-CT-2004-506242).
Keywords: 330; knowledge creation; interactive learning processes; industrial clusters; innovation policies; European integration; medium technology sectors; small and medium size firms